Deconstructing the Characteristics of the Ionized Gas Component in Planetary Nebulae From Their Internal Motions - López, J. A. (Frontiers in Astronomy and Space Sciences, 2022)
The internal motions of the ionized gas in the shells of planetary nebulae (PNe) have served as relevant diagnostic tools to understand the development of this important stage of evolution. This work highlights some of the kinematic studies that have impacted the most on the understanding of the structure and evolution of the envelope. These studies include the basic wind-driven isotropic expansion, the occurrence of complex shell morphology and unexpected fluis dynamics, such as high-speed, bipolar, collimated outflows. The current status on the subject and possible future trends are discussed in the closing remarks.